2007
DOI: 10.1111/j.1471-4159.2007.04987.x
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise counteracts the suppressive effects of peripheral lipopolysaccharide on hippocampal neurogenesis and learning and memory

Abstract: New neurons are continuously generated in hippocampal subgranular zone throughout life, and the amount of neurogenesis is suggested to be correlated with the hippocampusdependent function. Several extrinsic stimuli are known to modulate the neurogenesis process. Among them, physical exercise has advantageous effects on neurogenesis and brain function, while inflammation shows the opposite. Herein we showed that a moderate running exercise successfully restored the peripheral lipopolysaccharide (LPS)-impaired n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 47 publications
5
92
0
2
Order By: Relevance
“…Experimentally, systemic inflammation as induced by intraperitoneal administration of the Gram-negative bacterium-derived lipopolysaccharide (LPS) [19,20,21,22,23,24] or subcutaneous administration of Escherichia coli [25,26,27] has been shown to upregulate proinflammatory cytokine production and increase microglial activation in the rodent CNS. Furthermore, neonatal induction of central inflammation by subcutaneous E. coli administration reduces adult performance in hippocampus-dependent memory tasks, but only if a second peripheral LPS immune challenge is given in close temporal proximity to the test-learning phase [25], an effect attributed to reduced hippocampal neurogenesis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, systemic inflammation as induced by intraperitoneal administration of the Gram-negative bacterium-derived lipopolysaccharide (LPS) [19,20,21,22,23,24] or subcutaneous administration of Escherichia coli [25,26,27] has been shown to upregulate proinflammatory cytokine production and increase microglial activation in the rodent CNS. Furthermore, neonatal induction of central inflammation by subcutaneous E. coli administration reduces adult performance in hippocampus-dependent memory tasks, but only if a second peripheral LPS immune challenge is given in close temporal proximity to the test-learning phase [25], an effect attributed to reduced hippocampal neurogenesis [27].…”
Section: Introductionmentioning
confidence: 99%
“…• Decreased neurogenesis in the hippocampus, decreased hippocampal BDNF, and increased hippocampal TNF-α and IL-1beta were observed in LPS treated animals [51].…”
Section: Decreased Neurotrophic Factorsmentioning
confidence: 92%
“…Indeed, meta-analyses have demonstrated that serum BDNF is low in depressed patients (not taking antidepressants) compared to healthy controls and that serum BDNF levels increase with antidepressant treatment [50]. Studies have demonstrated that PICs may impact levels of neurotrophic factors [51]. See Table 1.…”
Section: Effects On Plasticity/neurogenesismentioning
confidence: 99%
“…In recent years, there have been many studies published on the proinflammatory functions of the cytokine IL-6 in the pathogenesis of several neurodegenerative disorders. However, due to the pleiotropic functions (acting both as a proinflammatory and an antiinflammatory) of IL-6, it is thought that the production of a determined level of IL-6 during moderate exercise can reverse the detrimental effects of uncontrolled inflammation by triggering the antiinflammatory effects of other cytokines (30). In an animal model showing the death of the hippocampal dentate granule cell layer after a chemical application, exercise attenuated neuronal death and diminished the elevation of the level of TNF-α, but this effect was undetectable in IL-6 knock-out mice (31).…”
Section: Discussionmentioning
confidence: 99%